Transcriptional Regulation of Osteoclastogenesis: The Emerging Role of KLF2 - Rolph, Daniela; Das, Hiranmoy (Frontiers in Immunology, 2020)
Dysregulation of osteoclastic differentiation and its activity is a hallmark of various musculoskeletal disease states. In this review, the complex molecular factors underlying osteoclastic differentiation and function are evaluated. The emerging role of KLF2 in regulation of osteoclastic differentiation is examined, specifically in the context of rheumatoid arthritis in which it has been most extensively studied among the musculoskeletal diseases. The therapies that exist to manage diseases associated with osteoclastogenesis are numerous and diverse. They are varied in their mechanisms of action and in the outcomes they produce. For this review, therapies targeting osteoclasts will be emphasized, though it should be noted that many therapies exist which bolster the action of osteoblasts. A new targeted molecular approach is under investigation for the future potential therapeutic development of rheumatoid arthritis.